Double-hump soliton excitations in an Antiferromagnetic spin lattice - Sheneiga J; Latha M.M (The Bioscan, 2026)
Using a modified Hamiltonian that takes into account both the bilinear and D- M interactions as well as the biquadratic anisotropic interaction, the dynamical theory of soliton excitation in a one-dimensional antiferromagnetic spin lattice is investigated. The two coupled nonlinear partial differential equations that govern the dynamics of the system are derived by introducing the Holstein -Primakoff transformation, the coherent state ansatz, and the time-dependent variational principle. The double- hump soliton propagation, the effect of interaction, and finally the inhomogenity parameters are examined by the Sine-Cosine function method.